2020
DOI: 10.1186/s12937-020-00578-0
|View full text |Cite
|
Sign up to set email alerts
|

Excess free fructose, apple juice, high fructose corn syrup and childhood asthma risk – the National Children’s Study

Abstract: Background: Recent research provides consistent evidence that the unexplained doubling of childhood asthma prevalence (1980-1995), its continued climb and 2013 plateau, may be associated with the proliferation of highfructose-corn-syrup (HFCS) in the US food supply. The HFCS used in soft drinks has been shown to contain a higher fructose-to-glucose ratio than previously thought. This coincides with a preference shift from orange to apple juice among young children. Apple juice naturally contains a high (≥2:1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
(177 reference statements)
0
23
0
Order By: Relevance
“…Second, several confounding factors have also influenced gut microbiome dysbiosis, such as geographical region, diet, and indoor/outdoor pollution. Third, changes in food composition were associated with intestinal flora disorder, especially the ratio of fructose to glucose (14,15); thus, it would have been valuable to evaluate participants for fructose malabsorption via a hydrogen breath test. Finally, our study did not include paired sputum samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, several confounding factors have also influenced gut microbiome dysbiosis, such as geographical region, diet, and indoor/outdoor pollution. Third, changes in food composition were associated with intestinal flora disorder, especially the ratio of fructose to glucose (14,15); thus, it would have been valuable to evaluate participants for fructose malabsorption via a hydrogen breath test. Finally, our study did not include paired sputum samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, excess drinks with free fructose probably lead to higher fructose/glucose ratios in the gut, which weakens intestinal absorption of fructose. The variation of microenvironment shifts the diversity of intestinal bacteria, which finally increases the incidence of asthma (14,15). Alterations in the gut microbiota early in life are associated with the risk of asthma (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of sugar-sweetened beverages (SSB) and fructose-rich fruit juices have been associated with markers of cardiometabolic disease, such as triglycerides (sugars are used for de novo lipogenesis) and HbA1c, as well as with increased risk of arthritis and asthma in pediatric populations, possibly due to increased fructose-induced AGEs formation, RAGE activation and inflammation [ 41 , 42 , 43 , 44 , 45 ]. A recent meta-analysis concluded that increased energy density of meals and food source (processed foods) are key determinants of fructose impact on glycemic control and insulinemia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that fructose malabsorption is a man made problem, as most natural foods contain a~1:1 fructose-to-glucose ratio [11]. It is noteworthy that epidemiological studies show that even moderate intake of high excess free fructose beverages (HFCS sweetened soda, fruit drinks, and apple juice) increases the risk [75,76] and prevalence of asthma [77][78][79][80][81][82][83][84][85][86], and young adult idiopathic arthris [87] -CHD comorbidities [88,89]. There were no associations with orange juice [75-77, 79, 87].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that epidemiological studies show that even moderate intake of high excess free fructose beverages (HFCS sweetened soda, fruit drinks, and apple juice) increases the risk [ 75 , 76 ] and prevalence of asthma [ 77 – 86 ], and young adult idiopathic arthris [ 87 ] – CHD co-morbidities [ 88 , 89 ]. There were no associations with orange juice [ 75 – 77 , 79 , 87 ]. The black/white CHD death disparity that began during the 1980’s corresponds with the black/white childhood asthma disparity [ 90 – 92 ] that inexplicably grew twofold from the 1980’s to 2010.…”
Section: Discussionmentioning
confidence: 99%